The Role of Customer Orientation and Islamic Work Environment in Enhancing Job Performance - faqih; Risma Rahmawati; Siti Nurhazwani Kamarudin (Journal of Islamic Enterpreneurship and Management, 2024)
This research begins with a research gap on the effect of customer orientation on job performance. This study aims to explore the role of responsiveness in leveraging customer orientation so as to improve performance from the perspective of the theory of planned behavior. This study uses quantitative methods with 77 respondents of sharia hotel employees. Based on data processing using the SPSS application, the results showed that customer orientation did not play a role in increasing job performance and responsiveness. However, to improve job performance, the Islamic work environment has proven to be successful in encouraging responsiveness which in turn improves job performance.